Evaluation of different premedicants in canine anaesthesia (Research in Agriculture Livestock and Fisheries, 2017)
Fifteen experimental trials were made in fifteen dogs in three different groups to study the degree of sedation produced by different premedicants, to evaluate and to compare their effects on various clinical parameters including different reflexes in dogs. These animals were premedicated with xylazine (1.1mg/kg), atropine (0.05mg/kg)-xylazine (1.1mg/kg) and diazepam (0.2mg/kg)-xylazine (1.1mg/kg) to observe their effect on different clinical and anaesthetic parameters. Diazepam-xylazine combination produced deep sedation while mild sedation was recorded with atropine-xylazine premedication. Respiration rate, heart rate and rectal temperature significantly decreased (P